A Model for Monetary Policy Analysis in Uruguay - Portillo, Rafael (IMF Working Papers; Working Paper, 2015)
Uruguay has recently reverted to a money targeting (MT) framework in the context of a disinflation strategy. We develop a quantitative model for monetary policy analysis incorporating money targets in the policy framework while also retaining a central role for interest rates in the transmission of policy. We use the model to show that tight financial conditions for a period may be necessary for inflation to converge to the middle of the target band. We also discuss various aspects of the MT framework. Two issues stand out. Excessive focus on hitting money targets can result in undesirable changes in the policy stance; while targets that incorporate elements of money demand forecasting are superior to targets that are excessively smooth or do not adjust for base effects.